ENGLISH PROVERBS IN A FOREIGN LANGUAGE AUDIENCE (TEACHING AND ASSESSING) (Ustozlar uchun, 2026)
The article is devoted to the linguistic and methodological aspects of English proverbs in a foreign language audience. Proverbs, as paremiological units reflecting the history and culture of the people, are of great cognitive value. In the process of teaching the proverbs of the English language in the Russian-speaking and Turkic-speaking audience, one should also rely on comparative research, which helps to identify similarities and differences. The method of introducing proverbs of the English language into a foreign-language audience ends with an assessment of the students’ knowledge, skills and abilities. Assessment methods and techniques are diverse: control questions, testing, tasks for speaking and writing, translation, etc. In the process of scientific research, such methods as descriptive, comparative, the method of control and assessment of knowledge were used.